Framework para calibração 4.0 de sensores analógicos: integração digital e interoperabilidade na metrologia 4.0 - Souza, Jerri Bernardes de (2024)
The transition to Industry 4.0 has brought a revolution in industrial processes, integrating advanced technologies to optimize production and data acquisition. In this context, Metrology 4.0 emerges as a key field, driving the digitalization and efficiency of metrological processes. Calibration 4.0, as part of this movement, leverages innovative techniques to enhance measurement accuracy, reduce operational time, and increase reliability in industrial processes that require periodic calibration. The primary objective of this study is to propose a framework for Calibration 4.0, specifically designed for analog sensors without digital communication protocols, enabling their integration into intelligent calibration systems. To achieve this, a methodology was developed to allow automatic data acquisition and the adaptation of these sensors to the requirements of Metrology 4.0. The research adopts a quantitative and qualitative approach, based on bibliometric analysis, a systematic literature review, and semi- structured interviews with experts. Based on this analysis, a structured framework was conceived, integrating reference standards with sensors under calibration, allowing their direct incorporation into the production process. The key findings indicate that adopting the proposed framework significantly reduces calibration time and operational costs by eliminating the need for manual calibrations and the transportation of sensors to specialized laboratories. Furthermore, the model improves measurement traceability and reliability, contributing to greater efficiency in industrial processes. The research also identified technical and operational challenges in implementing digital calibration for analog sensors, highlighting the importance of adaptable solutions for different industrial sectors. This study provides significant contributions to the industry by enabling the digitalization of calibration processes that traditionally require manual intervention. Its potential applications extend across various manufacturing sectors, ensuring greater efficiency, reliability, and alignment with Industry 4.0 practices, thereby promoting advancements in Metrology 4.0 and driving digital transformation in the sector.